Superconducting properties of multilayered thin film structure of YBCO with NiO and CoO fabricated by pulsed laser deposition - Din, Fasih Ud (2015)
This thesis attempts to investigate theoretical aspect of transport properties and experimental preparation of Yttrium Barium Copper Oxide (YBCO) single layer and multilayer thin films. Theoretical discussion on possible electrical transport properties on the basis of important experimental facts to satisfy the requirements of practical YBCO devices applications have not been addressed. The Pulsed Laser Deposition (PLD) is one of the techniques that is used to develop fine quality epitaxial thin films. In this research the bulk YBCO and NiO doped YBCO are prepared by different methods namely solid state reaction method and co precipitation method. The simulation modeling of laser plasma dynamics has been done in Matlab 2012 and different parameters have been proposed under the light of theoretical modeling. The theoretical transport properties have also been modeled which may provide some important utilization in electronic devices. The doping of NiO at Yttrium sites of the six samples with ratio from 0 - 0.1 exhibited tetragonal structure in pure while the orthorhombic structure in doped samples. The same orthorhombic structure has been found with decreased Tc values when the NiO has been added. AC susceptibility results indicate that the introduction of NiO during the final processing of YBCO bulk targets can decrease the Tc from 78-88K. Then PLD experiments were carried out on two different setups with different ranges of substrate heating systems, the former has 0-500ºC while other has 0-800ºC under oxygen and nitrogen ambient. The undertaken work involves two distinct studies, firstly, the YBCO epitaxial films and buffer layers have been probed numerically with the help of computer simulations. The simulations revealed the transport properties of the deposited YBCO thin films and analyzed the laser plasma dynamics and transport properties like resistive versus magnetic field and temperature, susceptibility measurements, the activation energy versus current density and high temperature thermal factor. The electrical transport properties of YBCO thin film have been investigated using different physical techniques. The physical transport properties were also estimated with temperature and magnetic fields limits using thermally-activated flux flow model with some modifications. The results of present simulation modelling have indicated that the magnitude of activation energy depends on temperature and magnetic field. The simulations revealed thickness dependent physical transport properties including electrical and magnetic properties of deposited YBCO thin films. The results have indicated that the temperature depends on the pinning energy and can be used to improve the superconducting properties (Tc) of the YBCO single layers thin films. The YBCO thin film have been experimentally fabricated in PLD system with substrate heater (> 750ºC) annealed in-situ for the 30 minutes after the deposition under oxygen ambient. The heating and cooling rate for annealing the deposited sample was 3ºC/min, and 2ºC/min, respectively to improve the quality of film layer. The YBCO target used in those experiment were prepared by amorphous phase epitaxy method. The same procedure for the YBCO/NiO(CoO) double layer and YBCO/NiO(CoO)/YBCO triple layer have been adopted. The results produce in the other PLD system with lower substrate heating system and ex-situ annealing via tubular furnace has not improved the quality of the layers either used by increasing heating rate and decreasing cooling rate. All the XRD diffraction peaks observed in bulk samples are also seen in the films. The XRD patterns have indicated that the crystalline quality of the thin film samples prepared by Amorphous phase epitaxy was better than those with co-precipitation method. Furthermore, based on FESEM images, it has proven that thicker and high substrate heating can absorb more oxygen and improve the surface layer.